SEMIOTIC ANALYSIS FOUND ON JORDAN PEELE HORROR MOVIE POSTER "US" - Endar Rachmawaty Linuwih; Eka Fadilah; Dimara, Willem Novaldi Gabriel (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
A movie poster conveys the main plot of the film, making it a popular medium for commercial advertising. In this way, movie studios might persuade more people to watch a certain film. As a result, the objective of this study is to use a semiotic method from Barthes to examine the message contained in the verbal and non-verbal parts of the Us movie poster. The data for this study were gathered using descriptive qualitative methods and a literature review. This study examines the verbal and non-verbal elements of a Us movie poster to show how they work together to convey meaning to the viewers and pique their attention. According to the study's findings, each symbol and sign (including verbal and nonverbal features) employed in the film effectively communicates its meaning by association. This study concludes that the signs and symbols utilized in the poster for the movie Us have a purpose and can effectively reflect, portray, and express that meaning.